Notch adaptive filter solution under unbalanced and/or distorted PCC voltage for 3-phase 3-wire shunt active power filter - Tuyen, N. D. (Springer Verlag, 2016)
In this paper, the 3-phase 3-wire Shunt Active Power Filter (ShAPF) dealing with non-ideal Point of Common Coupling (PCC) voltages will be presented. The instantaneous power theory is applied to design the ShAPF controller which shows reliable performances. The Adaptive Notch Filter (ANF) is proposed to process those unbalanced and/or distorted PCC voltage. The simulation results of Matlab/SimpowerSytem tool have proved that the ANF successfully facilitates the ShAPF in terms of compensating unbalanced/distorted current of loads under even without an ideal voltage circumstance.